2016
DOI: 10.1002/smll.201601993
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Integration‐Free Induced Neurons Using Graphene Oxide‐Polyethylenimine

Abstract: Direct conversion of somatic cells into induced neurons (iNs) without inducing pluripotency has great therapeutic potential for treating central nervous system diseases. Reprogramming of somatic cells to iNs requires the introduction of several factors that drive cell-fate conversion, and viruses are commonly used to deliver these factors into somatic cells. However, novel gene-delivery systems that do not integrate transgenes into the genome are required to generate iNs for safe human clinical applications. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…However, the low transfection and translation efficiencies of mRNA still remain a challenge. Currently, IVT mRNAs are complexed with structural elements, such as nanoparticles, polymers, or cationic lipids, to further improve intracellular stability and translational efficiency 23 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the low transfection and translation efficiencies of mRNA still remain a challenge. Currently, IVT mRNAs are complexed with structural elements, such as nanoparticles, polymers, or cationic lipids, to further improve intracellular stability and translational efficiency 23 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Since higher animals, including humans, do not have reverse transcriptase, there are no risks of integration of the transduced mRNAs into their genome. Many studies using mRNA transduction have been reported, e.g., hepatocytes, 59),115) cardiomyocytes, 116) neuronal cells, 40) endothelial progenitor cells, 117) and neural stem/ precursor cells. 34),118) Nevertheless, several difficulties of this method, such as stability and transfection efficiency, remain.…”
Section: Methods For Direct Cell Fate Conversionmentioning
confidence: 99%
“…Two very recent works demonstrated the application of GO-PEI complexes as mRNA and gene delivery vectors for direct reprogramming of human somatic cells into cells of neural and mesodermal lineage. 64,65 Baek et al demonstrated the reprogramming of¯broblasts into integration-free induced neurons (iNs) through the transfer of mRNA of neural lineage speci¯c reprogramming factors using GO-PEI complexes, that alleviated Parkinson's disease symptoms in a mouse model ( Fig. 3 (iii)).…”
Section: Graphene-based Nanomaterials For Nucleic Acid Deliverymentioning
confidence: 99%
“…3 (iii)). 64 In another study, Chiang et al demonstrated the direct reprogramming of human peripheral blood mononuclear cells into cells of the mesodermal lineage using GO-Fe 3 O 4 -PEI complexes carrying three episomal plasmids encoding pluripotent related factors via a process of combined magnetic stirring and photothermal stimulation to enhance the transfection e±ciencies of the complexes in suspension culture. 65 The transfected PBMCs were reprogrammed into iPSCs, which rapidly transdi®erentiated into mesodermal lineages without full reprogramming.…”
Section: Graphene-based Nanomaterials For Nucleic Acid Deliverymentioning
confidence: 99%
See 1 more Smart Citation